Die neue Weiterbildungsordnung – eine Herausforderung für die Viszeralchirurgie: Ergebnisse einer Umfrage unter DGAV-Mitgliedern und Lösungsstrategien der Jungen Chirurgie - Schardey, Josefine; Hüttl, Florentine; Jacobsen, Anne; Brunner, Stefanie; Tripke, Verena; Wirth, Ulrich; Werner, Jens; Kalff, Jörg C.; Sommer, Nils; Huber, Tobias (Die Chirurgie, 2024)
Background: The new competency-based further training regulations (nWBO) for surgical training have been adopted by all German state medical associations. Methods: From May to June 2023 the Young Surgeons’ Working Group (CAJC) conducted an anonymous online survey among the 5896 members of the German Society for General and Visceral Surgery (DGAV). Objective: The survey aimed to assess expectations regarding the nWBO and to develop strategies for enhancing surgical training. Results: With 488 participants (response rate 8.3%) the study is representative. The respondents consisted of 107 continuing education assistants (WBA 21.9%), 69 specialist physicians, and 188 senior physicians (specialist physicians 14.1% and senior physicians 38.5%), as well as 107 chief physicians (21.9%). The majority worked in regular care providers (44%), followed by maximum care providers (26.8%) and university clinics (20.1%). Only 22% considered the required operative spectrum of the new medical specialist training regulations (nWBO) to be realistic. Half of the respondents believed that full training in their clinic according to the new catalog will no longer be possible and 54.6% considered achieving the target numbers in 6 years to be impossible or state that they can no longer train the same number of continuing education assistants (WBAs) in the same time frame. Endoscopy (17.1–18.8%), fundoplication (15.4–17.7%) and head and neck procedures (12.1–17.1%) were consistently mentioned as bottlenecks across all levels of care. Rotations for balance were reported to be already established or not necessary in 64.7%. In 48% it was stated that the department had established the partial steps concept. The importance of a structured training concept was considered important by 85% of WBAs, compared to 53.3% of chief physicians (CÄ). If a structured training concept was present in the department, the achievability of the target numbers was significantly assessed more positively in the univariate analysis. In the multivariate analysis, male gender and the status of “habilitated/professor” were independent factors for a more positive assessment of the nWBO. Objective certification of training was considered important by 51.5%. Conclusion: Concerns surround the nWBO and the sentiment is pessimistic. Additional requirements and hospital reforms could exacerbate the situation. Collaboration and rotations are crucial but still insufficiently implemented. Quality-oriented certification could enhance the quality of training.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Competency-based education; Residency; Surgical training; Survey; Visceral surgery